T-cell lymphoma lines derived from rat thymomas induced by Moloney murine leukemia virus: phenotypic diversity and its implications. - Lazo, P A (1990)
The phenotype of 27 Moloney murine leukemia virus-induced rat thymic lymphomas and 36 cell lines derived from these tumors was determined by using 18 monoclonal antibodies directed against hematopoietic cell surface determinants. The cell lines and the primary tumors from which they were derived were clonally related as determined by the pattern of provirus integration and the pattern of rearrangement of the T-cell receptor beta and delta and Igh loci. The differentiation phenotype of the primary tumors and the cell lines derived from them were related. The differences observed between the primary tumors and the cell lines could be explained either by the selection of subpopulations of tumor cells during establishment in culture or by the phenotypic instability of the tumor cells. One cell line (LE3Sp) underwent the transition from a CD4+ CD8+ to a CD4+ CD8- phenotype following exposure to interleukin-2 in culture. Both the primary tumors and the cell lines derived from them express a wide range of phenotypes which correspond to multiple stages in T-cell development. This observation suggests that the pleiomorphism of retrovirus-induced lymphomas, which had been suggested previously from the analysis of mouse tumors, is an intrinsic property of the process of oncogenesis and is not due to the transformation of different types of cells by spontaneously arising leukemogenic variants of the inoculated virus. The wide spectrum of phenotypes expressed by these tumors suggests that Moloney murine leukemia virus may infect and transform T cells at various stages of development. Alternatively, the target cells may be immature T-cell precursors which, following transformation, continue to differentiate. A host of early findings, suggesting that the repertoire of target cells is restricted to poorly differentiated hematopoietic progenitors, and the ability of the LE3Sp cell line to differentiate in culture indicate that the latter possibility may be more likely. The data in this report address the extent and mechanism of the phenotypic variability of retrovirus-induced rodent T-cell lymphomas. In addition, they demonstrate the potential usefulness of the T-cell lymphoma lines we have established in studies of oncogenesis and T-cell differentiation.